Connexin-based signaling and drug-induced hepatotoxicity - Maes, Michaël (J Clin Transl Res, 2017)
Being critical mediators of liver homeostasis, connexins and their channels are frequently involved in liver toxicity. In the current paper, specific attention is paid to actions of hepatotoxic drugs on these communicative structures. In a first part, an overview is provided on the structural, regulatory and functional properties of connexin-based channels in the liver. In the second part, documented effects of acetaminophen, hypolipidemic drugs, phenobarbital and methapyriline on connexin signaling are discussed. Furthermore, the relevance of this subject for the fields of clinical and in vitro toxicology is demonstrated. Relevance for patients: The role of connexin signaling in drug-induced hepatotoxicity may be of high clinical relevance, as it offers perspectives for the therapeutic treatment of such insults by interfering with connexin channel opening.